Adeno-associated virus-mediated knockdown demonstrates the major role of hepatic Bcrp in the overall disposition of the active metabolite of the tyrosine kinase inhibitor regorafenib in mice. (April 2023) - Alshammari, Aya Hasan; Masuo, Yusuke; Yoshino, Shotaro; Yamashita, Reiya; Ishimoto, Takahiro; Fujita, Ken-ichi; Kato, Yukio
Abstract: Breast cancer resistance protein (BCRP) is expressed on hepatic bile canalicular membranes; however, its impact on substrate drug disposition is limited. This study proposes an in vivo knockdown approach using adeno-associated virus encoding short hairpin RNA (shRNA) targeting the bcrp gene (AAV-shBcrp) to clarify the substrate, the overall disposition of which is largely governed by hepatic Bcrp. The disposition of the tyrosine kinase inhibitor, regorafenib, was first examined in bcrp gene knockout (Bcrp −/− ) and wild-type (WT) mice, as it was sequentially converted to active metabolites M − 2 and M − 5, which are BCRP substrates. After oral administration of regorafenib, plasma and liver concentrations of M − 5, but not regorafenib, were higher in Bcrp −/− than WT mice. To directly examine the role of hepatic Bcrp in M − 5 disposition, M − 5 was intravenously injected into mice three weeks after the intravenous injection of AAV-shBcrp, when mRNA of Bcrp in the liver (but not the small intestine) was downregulated. AAV-shBcrp-treated mice showed higher M − 5 concentration in plasma and liver, but lower biliary excretion than the control mice, indicating the fundamental role of hepatic Bcrp in M − 5 disposition. This is the first application of AAV-knockdown strategy to clarify the pharmacokinetic role of xenobiotic efflux transporters in the liver. Graphical abstract: Image 1